Proceedings of the IEEE International Symposium on Industrial Electronics, 2005. ISIE 2005. 2005
DOI: 10.1109/isie.2005.1529167
|View full text |Cite
|
Sign up to set email alerts
|

A Mechatronic Design for Robotic Deburring

Abstract: This paper deals with the implementation of a mechatronic methodology for the robotic deburring of planar workpieces with an unknown shape performed by an industrial manipulator. The approach is based on the use of a hybrid force/velocity control law and on a correlated suitable design of the adopted deburring tool. Experimental results, obtained with a two degrees-of-freedom SCARA industrial robot manipulator, show the effectiveness of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Contour following has become a benchmark in literature, as it represents a challenging task requiring accurate force control, and is also integral to many industrial applications (e.g. grinding [12], deburring [13], shape recovery [14]). Even though this task can be accomplished using only sensor feedback and without the use of an estimator, it has been shown that the use of an estimator can improve the tracking accuracy [5].…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Contour following has become a benchmark in literature, as it represents a challenging task requiring accurate force control, and is also integral to many industrial applications (e.g. grinding [12], deburring [13], shape recovery [14]). Even though this task can be accomplished using only sensor feedback and without the use of an estimator, it has been shown that the use of an estimator can improve the tracking accuracy [5].…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…1) can be suitable compensated using cutting force models (Duelen, G.;Munch, H.;Surdilovic, D.;Timm, J. 1992) or measuring the torque of the milling spindle Visioli, A. 2005).…”
Section: Problem Formulationmentioning
confidence: 99%
“…This proposed system is capable of correcting the tool path and maintaining an adequate contact between the robot tool and part edge. Much of the research involved in the area of control methods can be categorised into two major approaches: impedance control (Cohen and Flash, 1991; Carelli and Kelly, 1991; Wang et al , 2006a, b) and hybrid position/force control (Pires et al , 2002; Goradia et al , 2002; Robertsson et al , 2006; Pires and Afonso, 2007; Ziliani et al , 2005, 2007). These methods require an accurate model of force interaction between the manipulator and the environment and are difficult to implement on typical industrial manipulators that are designed for position control.…”
Section: Introductionmentioning
confidence: 99%